Civic Knowledge and Civic Skills in Social Studies as Predictors of Patriotic Citizens among Undergraduate Social Studies Students in the University of Jos, Nigeria - Shittu Lukman Olayinka; Garba Muftahu Abdullahi; Christiana Ochanya Abah; Salahuddin (Britain International for Academic Research (BIAR) Publisher, 2024)
This study investigated civic skills and civic knowledge as predictors of patriotism among undergraduate students in the University of Jos. The study was guided by three objectives and three corresponding research questions were answered. The study used a survey research design specifically cross-sectional survey research design. The population was made up of 1,457 students of social studies and students taking social studies as elective across 100 to 400 levels in the Department of Social Science Education University of Jos. A sample of 400 students were selected using proportional stratified technique. A structured questionnaire was used for data collection developed by the researcher. The questionnaire was subjected to face and content validity by experts. The reliability was established at 0.76. The data collected were analysed using descriptive and inferential statics of mean and standard deviation through SPSS. The analysis revealed among other things that that, the corruption and impunity in the Nigeria society as well as inequality, lack of social justices, poor leadership and poor citizenship education are causes of poor patriotism among undergraduate students s shown in the study. The study recommended among other things that, there should a robust curriculum review to promote holistic teaching and inculcation of civic knowledge and skills in students for patriotism.